El estado nutricional como riesgo para desarrollar caries en niños menores de cinco años de edad - Campodónico Reátegui, Carlos (2001)
It was evaluated the weight and height of 101 children, 3 to 5 year-old, from the marginal urban area "Playa Rimac " of Lima city, to determine their nutrition state, and know the influence that can exist with d.m.f. Index. There was 1% of children with malnutrition "moderate", 15% with malnutrition "light", 72% nutritional state "normal", and 12% in state of "obesity", no one with "severe" malnutrition. The mean d.m,f Index was 4,7 even arriving at 6,6, although it showed the tendency to be elevated in cases of malnutrition, there was not a positive statistical correlationy as it happened to Oral Hygiene Index, since 61 % qfthe children presented a high level of plaque.